Effect of varying recovery duration on postactivation potentiation of explosive jump and short sprint in elite young soccer players - Köklü, Y.; Köklü, Ö.; Isikdemir, E.; Alemdaroglu, U. (The Journal of Strength and Conditioning Research, 2022)
The purpose of this study was to investigate the effects of postactivation potentiation (PAP) on vertical jump and sprint performances with different recovery durations. Twelve elite young soccer players (average age: 17.0 ± 0.6 years; body mass: 67.0 ± 5.4 kg; height: 175.0 ± 3.5 cm) voluntarily performed countermovement jump (CMJ) and 30-m sprints (with 10-m split times) under unloaded and 4 different recovery duration conditions (R1: 1 minute, R2: 2 minutes, R3: 3 minutes, and R4: 4 minutes) after a set of 3 repetitions of half-squat exercises at 90% of 1-repetition maximum. Electromyographic assessments of both limbs' vastus lateralis (VL) and semitendinosus (ST) muscle activity were also made during the tests. Vertical jump height, sprint time, and VL and ST muscle activity root mean square (RMS) values were analyzed. The results show that players demonstrated significantly better CMJ, 10-, and 30-m sprint performances in the R4 condition compared with the unloaded condition (p < 0.05). The players also showed significantly higher RMS values for VL and ST muscle activity in the CMJ and 30-m test performances for both legs in the R4 condition compared with the unloaded, R1, R2, and R3 conditions (p < 0.05). According to these results, if sports scientists and coaches desire to increase the PAP effect after heavy resistance training, 4 minutes of recovery time instead of 1, 2, or 3 minutes for CMJ, 10-, and 30-m sprint performances is recommended,